Electromyographic study of the trapezius (pars superior) and levator scapulae muscles in circumduction and pendular oscillation of the arm - Longo Bull, M.; De Freitas, V.; Vitti, M. (My University, 1984)
The trapezius (pars superior) and levator scapulae mm were studied in the arm movements of circumduction and pendular oscillation in 30 adult volunteers of both sexes. A two-channel TECA TE 4 electromyograph and single coaxial needle electrodes were used. It was found out that as arm conduction, both muscles show an activity that gradually increases and decreases the intensity at the elevation and lowering phases respectively. It was also noticed that between two consecutive circumductions a 'silent period' in the activity of the above mentioned muscles occurs. In pendular oscillation these muscles show electrical activity both in the forward and backward moving, and both muscles show a 'silent period' when the arm passes by the trunk. It was not observed in these movements any significant difference in activity of these muscles regarding sex.
Keywords: arm movement; diagnosis; electromyography; human; human experiment; levator scapulae muscle; muscle; musculoskeletal system; normal human; trapezius muscle; Adult; Arm; Electromyography; Female; Human; Male; Movement; Muscles; Support, Non-U.S. Gov't